Implementasi Budaya Religius dalam Upaya Meningkatkan Kecerdasan Spiritual Peserta Didik - Mamun Zahrudin; Shalahudin Ismail; Uus Ruswandi; Bambang Samsul Arifin (Asatiza: Jurnal Pendidikan, 2021)
This study aimed at describing how the implementation of religious culture in increasing the spiritual intelligence of participants in schools. This study used a qualitative descriptive method with the objectives being studied were students of MI Terpadu Ad-Dimyati Bandung. The data collection techniques used were interviews, observation, and documentation. The results showed that the implementation of religious culture in increasing the spiritual intelligence of students through smiling, greeting, and greeting (3S), Tausiah, reading short surahs, and Asmaul Husna, prayer zuhr in the congregation, Dhuha prayer, Istighasah, and Infaq (Gerakan Dua Bumi-The movement of Two Earths) have met the criteria for increasing the spiritual intelligence of students. Because as an Islamic educational institution, the school is not only concerned with cognitive aspects but also good habituation and spiritual concepts that can be applied in everyday life. This research is expected to broaden the writer's insight, especially and generally for readers. Whereas for schools the implementation of religious culture to improve the spiritual intelligence of students should involve the participation of families and communities so that the increase in spiritual intelligence is more optimal